HETROGENOUS WOMAN CHARACTERS IN THE NOVELS OF PREETY SHENOY - P KalyaniSwapna, DR R Naga Dhana Lakshmi (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
PreetiShenoyis the principalnovelist who reaches with a freshdocument and apprehends it being transformed into a finished book. Her writings started with the purpose to permitambitious and debutant characters and tie them to readers. She has been a fictionalsupport of the society and has been inculcating the reading habit for the last 10 years, now takes a step ahead to inculcate and curate the problem solving skills too by connecting authors to readers. Shenoy takes care of all the themes like young woman, motherhood, single parent, educated woman, and most important thing of all is marketing and sales at bookstores as well as most online bookstores in India. The year was 2011. It was the dawn of Shenoy writings. The first novel would soon be making waves, and readers were not far behind. In the midst of this exciting era of change, an ambitious new writer was setting out to radically rethink the way pens were designed. Shenoy philosophy is to put readers first and this is what makes Shenoy the most recognized fine writing brand globally. She again created history by writing the second novel in 2014. Shenoy is a pioneer in the writing novels, in 1996. Today, she is an exclusive range of fine writer who is only available in India. In last 9 years Shenoy has made such a mark on the nation that she has been awarded “Indian of the year” by Brands Academy. As a writer, Shenoy has served readers impeccably with her writings that are a perfect combination of elegance, reliability, durability and timeless style. Her writings are inspirational and a prized possession for Indian populace. The Indian English writers offer a vast potential that can be tapped with the right steps Indian English literature was created in the face of intolerance and discrimination to reaffirm faith in the dignity and worth of humans, and in the equal rights of women and men. Its fundamental values postulated that in order to live sustainably, we must practise tolerance and endorse the values of equality. However, if we are to stay true to the ethical and moral values.